Students’ Morphological Errors in Writing Recount Text at Muhammadiyah University of Metro - Fitri Palupi Kusumawati (Premise: Journal of English Education and Applied Linguistics, 2015)
The objectives of this research are to find out the kinds of students’ morphological error in writing recount text and to find out the difficulties faced by the student in writing recount text. This research is a descriptive qualitative. It means this study focused to describe and analyze the students’ error. Based on the result that mentioned previously, the researcher found that the number of students’ omission and misformation errors are high. The highest students’ errors made in misformation are about 51, 19 %.  Most of the students used wrong form of morphological in their writing. The second is the students errors made in omission are around 32, 74 %.The students not adding bound morpheme, they omit the necessary item in their sentences. The third, the students made errors in addition and misordering are about 13, 69 % and 2, 38 %. The students add unnecessary item and put incorrect placement of morpheme in their writing. On the other hand, according to table 4.2 the researcher conclude that the number of error is five or 31, 25 % students made error in global error and 11or 68, 75 % students made in local error. Key Words: Morphological errors, students’ writing